All-optical ultra-wideband doublet signal source based on the cross-gain modulation in a semiconductor optical amplifier - 赵赞善 李培丽 郑加金 潘婷婷 黄世杰 罗友宏 (Optoelectronics letters, 2012)
We propose a novel scheme to generate the ultra-wideband （UWB） doublet signal pulse based on the cross-gain modulation （XGM） in a semiconductor optical amplifier （SOA）. In the scheme, only an optical source and an SOA are needed. As there is only one wavelength included in the output doublet signal pulse, no time difference between the upper and down pulses is introduced during the transmission process. By using the software of Optisystem 7.0, the impacts of the optical power, the SOA current, the wavelength and the input signal pulse width on the generated doublet pulse are simulated and tudied numerically. The results show that when the pulse width of the input signal pulse is larger, the output signal pulse is better, and is insensitive to the change of wavelength. In addition, the ultra-wideband positive and negative monocycles can be generated by choosing suitable optical source power and SOA current.